Analyzing the business process of the Religious Court in Surabaya using the Business Process Modeling Notation (BPMN) method.: Analisa Proses Bisnis Pengadilan Agama Surabaya Menggunakan Metode Business Process Modelling Notation (BPMN) - Syarifudin, Muhammad Rois; Bisma, Rahadian (Journal of Emerging Information Systems and Business Intelligence (JEISBI), 2023)
Every agency must have a goal to make each process effective and efficient. The Bsinsi process is one aspect that can influence the level of effectiveness and efficiency in an agency. The Surabaya Religious Court is one of three special courts in Indonesia which is located in Surabaya. There are several business processes at the Surabaya Religious Court including the registration process, payment process, inheritance registration process, divorce registration process, joint property case registration process, process minor marriage registration, mediation process, and trial process. The purpose of this research is to test and simulate the effectiveness and efficiency of business procedures used in the Surabaya Religious Courts. Analysis of the Surabaya Religious Court Business Process Using MethodsBusiness Process Modelling Notation (BPMN). Many difficulties were discovered during the study and modeling of business processes that might hinder the operation of each process, and the researcher then presented business process suggestions with various factors for decision making. The Surabaya Religious Court becomes more effective and efficient with the business process ideas proposed by the author.